2017
DOI: 10.1017/ice.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Clostridium difficile Infection in Hematology-Oncology Patients Colonized With Toxigenic C. difficile

Abstract: The prevalence of colonization with toxigenic Clostridium difficile among patients with hematological malignancies and/or bone marrow transplant at admission to a 566-bed academic medical care center was 9.3%, with 13.3% of colonized patients developing symptomatic disease during hospitalization. This population may benefit from targeted Clostridium difficile infection control interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…Similar to a recent adult study, our data show that pediatric patients who are asymptomatically colonized at admission are at the highest risk of developing CDI during that admission. We also show that this subsequent CDI is almost exclusively related to the patient's own colonized strain, and not related to other patients’ strains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to a recent adult study, our data show that pediatric patients who are asymptomatically colonized at admission are at the highest risk of developing CDI during that admission. We also show that this subsequent CDI is almost exclusively related to the patient's own colonized strain, and not related to other patients’ strains.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to a recent adult study, 22 band, which is still considered closely related. 23 This is the fundamental finding of this study, and has two major implications.…”
Section: Discussionsupporting
confidence: 84%
“…The median age for C difficile positivity in the PTP and NTP was 6.1 and 5.8 years, respectively, with the PTP having a lower percentage of positive tests in patients <2 years old. Beyond infancy, higher rates of colonization and prolonged shedding in stool have been demonstrated in similar populations and are also likely contributing factors 18‐23 …”
Section: Discussionmentioning
confidence: 95%
“…As discussed above, a fiber-deficient diet has been shown to hinder clearance of C. difficile after challenge (15) . This is particularly relevant in a clinical context as recent studies of both pediatric and adult oncology patients have shown asymptomatic colonization rates with C. difficile of ∼30% and ∼10%, respectively (3, 31) . Further, in pediatric patients it was demonstrated that the vast majority of “hospital-acquired” CDI may be caused by a strain of C. difficile that is present at admission rather than a strain acquired during the patient stay (3) .…”
Section: Discussionmentioning
confidence: 99%